Optimising RNA extraction for paddy bulk soil samples for metatranscriptome sequencing - Sumitra Sivaprakasam; Tan Yee Fan; Yukgehnaish Kumarasan; Erneeza Mohd Hata; Ganesan Vadamalai; Bent Petersen; Thomas Sicheritz-Pontén; Sivachandran Parimannan; Heera Rajandas (BMC Research Notes)
Abstract Objective Extraction of high-quality RNA is crucial for understanding the molecular dynamics of microbiomes in the growth and development of paddy plants. However, paddy soil poses challenges due to contaminants such as humic substances and its clayish nature, which lead to RNA adsorption and reduced yield. This study aimed to improve existing RNA extraction methods for bulk soil samples collected from a paddy field in Perak, Malaysia. We first evaluated different published protocols, selected the best based on RNA yield and quality, and further optimized it for highly pigmented soil samples. The resulting RNA was subjected to metatranscriptome sequencing, de novo assembly and annotation. Results Upon evaluation, the RNA extraction protocol by Peng et al., 2018 (method B3) was optimized by incorporating 20% and 30% PEG-based precipitation to remove carry-over pigmentation. Comparative testing showed that 20% PEG produced the highest quality RNA, yielding pigment-free RNA (> 100 ng/µl, integrity > 7, and A260/A280 of 2.02 ± 0.02). Metatranscriptome sequencing and analysis with Trinity, BUSCO, and Kraken2 confirmed superior quality and higher bacterial read assignment for RNA extracted with 20% PEG, highlighting its effectiveness for downstream microbial transcriptomic applications.